Elimination of ethanethiol released from municipal wastes by absorption sequencing electrochemical oxidation. Issue 13 (18th July 2017) - Gong, Xiao; Yang, Xu; Zheng, Haoyue; Wu, Zucheng
ABSTRACT: As a typical municipal waste landfill gas, ethanethiol can become an air pollutant because of its low odor threshold concentration and toxicity to human beings. A hybrid process of absorption combined with electrochemical oxidation to degrade ethanethiol was investigated. The ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM]BF4 ) was employed as an absorbent to capture ethanethiol from the air stream. Electrochemical oxidation demonstrated that ethanethiol could be oxidized on a β-PbO2 anode modified with fluoride, while [BMIM]BF4 was used as an electrolyte. After a reaction time of 90 min under a current density of 50 mA/cm 2, ethanethiol could be thoroughly destructed by the successive attack of hydroxyl radicals (·OH) electrogenerated on the surface of the β-PbO2 anode, while the sulfur atoms in ethanethiol were ultimately converted to sulfate ions . The reaction mechanism is proposed, and the operating condition is also estimated with a kinetic model. This hybrid process could be a promising way to remove thiol compounds from municipal waste landfill gases.